Utilização de medicamentos em adultos no município de Praia Grande, São Paulo: prevalência e fatores associados - Vieira, Marlene Rosimar da Silva (2016)
Introduction: The guarantee of the right to health includes access to medicines. In Brazil we can´t consider this access only with the public sector in view; because even being a country with universal health care system, 26% of the population is affiliated to the private health insurance and the drug purchasing expenses correspond to 48.6 % of the average monthly expenditure on health of Brazilian families. Objective: To analyze the use of medication and associated factors for the adult population in the municipality of Praia Grande, Sao Paulo. Methodology: Cross-sectional population-based study that included 985 adults of both sexes. Cluster sampling in two stages, in Praia Grande, São Paulo, 2012. The dependent variables were the use and access to medicines through the public health system. The independent variables were sociodemographic and health status characteristics. The Poisson model with robust variance was the method of analysis. Spending and commitment of the income generated by the acquisition in private pharmacies were also checked, and possible drug interactions. Results: The prevalence of drug use in the population studied was 47.9%. Elderly had a higher prevalence of drug use (61.2%) compared to adults (42.4%). Being woman, having attended a health service in the last year, have chronic disease, more than eight years of study and consider bad health were variables associated with the use of drugs. The drugs used were obtained in its entirety in public pharmacies by 58.7% of users, which was associated to have chronic illness, have attended a health service in the last year, not having private health insurance and being female. The monthly private spending on drugs was on average R$ 17.00 and the commitment of income was higher for males, with higher education, the private health sector as a reference, with health insurance and chronic illness. The possibility to have a drug interaction was associated with the highest number of drugs used and not with the model of health service used, public or private. Conclusions: The prevalence of drug use in the city was similar to the national. The public health system is promoting access to medicines in the city, especially for patients with chronic diseases and women. Private spending on drugs is higher with the share of the population with the highest incomes. Incorporating the practice of assessing possible drug interactions in primary care, especially for some groups of patients, may be a strategy to improve the quality of pharmaceutical care.